Privacy protection scheme based on fair blind signature and hierarchical encryption for consortium blockchain - Xuewang ZHANG; Zhihong LI; Jinzhao LIN (Tongxin xuebao)
To solve the security hazards of identity information and transaction data and the time-consuming problem of traditional single-level encryption methods in the current application scenarios of consortium blockchain, a privacy protection scheme of consortium blockchain based on fair blind signature and hierarchical encryption was proposed.Considering the strong centrality and poor security of the existing fair blind signature scheme, it was redesigned with zero-knowledge proof technology to be applicable for consortium blockchain application scenario.Based on the Paillier homomorphic encryption algorithm, a supervisable hierarchical encryption method was designed, and the method realized the supervision of encrypted transaction data information and reduced the time cost of the encryption and decryption process.The security analysis and simulation results show that the proposed scheme can effectively resist malicious attacks such as tampering and eavesdropping and significantly improve the encryption efficiency.